2016
DOI: 10.1158/1078-0432.ccr-15-1191
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting of BCL2 Family Proteins with ABT-199 and Homoharringtonine Reveals BCL2- and MCL1-Dependent Subgroups of Diffuse Large B-Cell Lymphoma

Abstract: Purpose: To investigate the roles of BCL2, MCL1, and BCL-XL in the survival of diffuse large B-cell lymphoma (DLBCL).Experimental designs: Immunohistochemical analysis of 105 primary DLBCL samples, and Western blot analysis of 18 DLBCL cell lines for the expression of BCL2, MCL1, and BCL-XL. Pharmacologic targeting of BCL2, MCL1, and BCL-XL with ABT-199, homoharringtonine (HHT), and ABT-737. Analysis of DLBCL clones with manipulated expressions of BCL2, MCL1, and BCL-XL. Immunoprecipitation of MCL1 complexes i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 24 publications
7
88
0
Order By: Relevance
“…Targeted inhibition of BCL2 with its highly selective inhibitor ABT-199 recently emerged as a promising treatment strategy for some B-cell malignancies such as CLL and MCL (26,27). ABT-199 was proved potentially effective in BCL2 positive DLBCL (28). In GCB-DLBCL with BCL2 positive might benefit from ABT-199 or other inhibitors of BCL2 function.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted inhibition of BCL2 with its highly selective inhibitor ABT-199 recently emerged as a promising treatment strategy for some B-cell malignancies such as CLL and MCL (26,27). ABT-199 was proved potentially effective in BCL2 positive DLBCL (28). In GCB-DLBCL with BCL2 positive might benefit from ABT-199 or other inhibitors of BCL2 function.…”
Section: Discussionmentioning
confidence: 99%
“…1B), which is frequently coexpressed with BCL-2 in DLBCL patient samples and cell lines (63). BCL-2 and MCL-1 dependent subgroups can be identified by pharmacological targeting of the two proteins (64). Single-agent treatment with venetoclax was found to induce only modest antitumor activity against certain DLBCL cell lines and resulted in a compensatory increase in expression of MCL-1 (63).…”
Section: Identifying Sensitive Tumor Types and Likely Respondersmentioning
confidence: 99%
“…76 Another study also showed that concurrent inhibition of BCL-2 and MCL-1 with ABT-199 and homoharringtonine, a plant alkaloid, could induce significant synthetic lethality in most BCL-2-expressing DLBCL cell lines. 77 MCL-1 is widely and highly expressed in MM, and it is also an attractive therapeutic target. 78 Recently, a novel MCL-1 inhibitor S63845 was reported to be tolerable and effective in diverse cancer models, 35 making it possible to overcome venetoclax resistance in various types of B-cell lymphoid malignancies.…”
mentioning
confidence: 99%